Methionine Sulfoxide Reductase A Is Important for Lens Cell Viability and Resistance to Oxidative Stress - Kantorow, Marc; Hawse, John R.; Cowell, Tracy L.; Benhamed, Sonia; Pizarro, Gresin O.; Reddy, Venkat N.; Hejtmancik, J. F.; Weissbach, Herbert (Proceedings of the National Academy of Sciences - PNAS, 2004)
Age-related cataract, an opacity of the eye lens, is the leading cause of visual impairment in the elderly, the etiology of which is related to oxidative stress damage. Oxidation of methionine to methionine sulfoxide is a major oxidative stress product that reaches levels as high as 60% in cataract while being essentially absent from clear lenses. Methionine oxidation results in loss of protein function that can be reversed through the action of methionine sulfoxide reductase A (MsrA), which is implicated in oxidative stress protection and is an essential regulator of longevity in species ranging from Escherichia coli to mice. To establish a role for MsrA in lens protection against oxidative stress, we have examined the levels and spatial expression patterns of MsrA in the human lens and have tested the ability of MsrA to protect lens cells directly against oxidative stress. In the present report, we establish that MsrA is present throughout the human lens, where it is likely to defend lens cells and their components against methionine oxidation. We demonstrate that overexpression of MsrA protects lens cells against oxidative stress damage, whereas silencing of the MsrA gene renders lens cells more sensitive to oxidative stress damage. We also provide evidence that MsrA is important for lens cell function in the absence of exogenous stress. Collectively, these data implicate MsrA as a key player in lens cell viability and resistance to oxidative stress, a major factor in the etiology of age-related cataract.